A novel metal-free synthesis of thiazole-substituted α-hydroxy carbonyl compounds and 2-alkenylthiazoles from thiazole N-oxides and olefins. Issue 51 (19th December 2019) - Li, Hui; Zhang, Juan; Zhang, Yanqiu; Wang, Jiayi; Song, Gonghua
Graphical abstract: Highlights: A metal-free and atom-economic synthesis of thiazole-substituted α-hydroxy carbonyl compounds has been established. A domino 1, 3-dipolar cycloaddition and ring-opening aromatization reaction was involved. The corresponding 2-alkenylthiazoles were produced in excellent yields through a one-pot, two-step dehydration process. Abstract: A metal-free and highly atom-economic synthesis of thiazole-substituted α-hydroxy carbonyl compounds has been developed. Catalyzed by 5 mol% of p -toluenesulfonic acid (TsOH), a variety of thiazole-substituted α-hydroxy carbonyl compounds were obtained in moderate to good yields via 1, 3-dipolar cycloaddition of thiazole N -oxides with olefins, followed by a ring-opening reaction. Furthermore, the corresponding 2-alkenylthiazoles could be produced in excellent yields from synthesized α-hydroxy carbonyl compounds through a one-pot, two-step dehydration process.